Influence of Palladium on Ni-based Catalyst for Hydrogen Production via Thermo-catalytic Methane Decomposition - Lock, Irene S. M.; Lock, Serene S. M.; Vo, Dai-Viet N.; Abdullah, Bawadi (The Italian Association of Chemical Engineering-AIDIC, 2017)
This study investigates the effect of introducing palladium (Pd) as a promoter on the catalytic performance of Ni/Al2O3 catalysts which were prepared by wet impregnation method at various reaction temperatures. The catalytic activity, thermal stability and deactivation rate of the synthesized catalysts were evaluated at atmospheric pressure on a conventional fixed bed reactor at the temperature ranges of 8731073 K for 4 h at constant methane flow-rate. The results suggested that the introduction of Pd on Ni/Al2O3 can significantly enhance the catalytic activity of the catalysts. A slower deactivation rate was observed for Ni-Pd/Al2O3 catalyst. This is due to the positive effect of Pd on metallic Ni particles, improving the ability of the catalyst to accumulate carbon, thus enhancing the thermal stability at elevated temperatures.